2001
DOI: 10.1073/pnas.091100598
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of a grid-mounted molecular dipolar rotor in a rotating electric field

Abstract: Classical molecular dynamics is applied to the rotation of a dipolar molecular rotor mounted on a square grid and driven by rotating electric field E() at T Ӎ 150 K. The rotor is a complex of Re with two substituted o-phenanthrolines, one positively and one negatively charged, attached to an axial position of Rh 2 4؉ in a [2]staffanedicarboxylate grid through 2-(3-cyanobicyclo[1.1.1]pent-1-yl)malonic dialdehyde. Four regimes are characterized by a, the average lag per turn: (i) synchronous (a < 1͞e) at E() ‫؍‬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 35 publications
(33 reference statements)
2
103
0
Order By: Relevance
“…2, a set of periodic rotary potentials suggests that rotators with a given rotational symmetry order (C n ) will have energy profiles with "n" minima and maxima, angular displacements of 360∕n°, and barriers that become smaller as the rotator approaches the shape of a cylinder when n → ∞. As the number of energy minima n increases, there is a greater spatial resolution that may be addressed with external stimuli when a suitable dipole is included in the structure (18,19). Increasing the symmetry of the rotators is also interesting because it allows the formation of gears with n teeth when the vertices of the rotator are extended in a radial manner.…”
mentioning
confidence: 99%
“…2, a set of periodic rotary potentials suggests that rotators with a given rotational symmetry order (C n ) will have energy profiles with "n" minima and maxima, angular displacements of 360∕n°, and barriers that become smaller as the rotator approaches the shape of a cylinder when n → ∞. As the number of energy minima n increases, there is a greater spatial resolution that may be addressed with external stimuli when a suitable dipole is included in the structure (18,19). Increasing the symmetry of the rotators is also interesting because it allows the formation of gears with n teeth when the vertices of the rotator are extended in a radial manner.…”
mentioning
confidence: 99%
“…Grimzewski et al [3] observed rotation of a single molecule within a supramolecular bearing. After the first examples of unidirectional rotating molecular motors based on simple organic molecules [4,5], several works reported on this subject [6][7][8][9][10][11][12][13][14]. Also great theoretical efforts have been devoted to understanding and proposing nanoscale rotors and stators as molecular motors capable of transforming a driven random rotation efficiently into a directed translational motion [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…This approach may serve as alternative to chemical, electrochemical or photochemical stimuli of molecular rotors [4][5][6][7][8][9], which is an important challenge in molecular engineering [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%